Kepemimpinan Progresif atasi Kemunduran Pendidikan Islam Tradisional - Ja'far Nahsir; Asep Awaluddin (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2021)
Problems in traditional Islamic education start from an unattractive outward appearance to low competitiveness when juxtaposed with modern educational institutions. So it is necessary to find out the reasons for the decline of traditional Islamic educational institutions. This research is descriptive qualitative research with library-based data collection. The results of this study indicate that there is a need for leadership reformulation in traditional Islamic educational institutions so that they can exist and have high competitiveness, namely by utilizing the progressive leadership model as exemplified by the Prophet Muhammad SAW, namely 1) selecting staff who have the most role in running the organization in a professional and applicable way. fair, 2) able to take advantage of the development of information technology and also social media to convey messages and at the same time promote in the era of information technology ABSTRAK Permasalahan dalam Pendidikan Islam tradisional dimulai dari penampilan luar yang kurang menarik hingga daya saing yang rendah jika disandingkan dengan lembaga pendidikan modern. Sehingga perlu dicari tahu sebab mengenai kemunduran lembaga-lembaga pendidikan Islam tradisional. Penelitian ini adalah penelitian kualitatif deskriptif dengan pengumpulan data berbasis kepustakaan. Hasil penelitian ini menunjukkan bahwa perlu reformulasi kepemimpinan pada lembaga pendidikan Islam tradisional sehingga mereka mampu eksis dan berdaya saing tinggi, yaitu dengan memanfaatkan model kepemimpinan progresif sebagaimana dicontohkan oleh Nabi Muhammad SAW yaitu 1) memilih staf yang paling berperan menjalankan roda organisasi dengan cara profesional dan berlaku adil, 2) mampu memanfaatkan perkembangan teknologi informasi dan juga media sosial guna menyampaikan pesan dan sekaligus berpromosi di era teknologi informasi. Kata Kunci: pemimpin, kemunduran, progresif.